Neutrophil-related gene expression profile is associated with future paediatric bronchiectasis exacerbations - Hannah E. O’Farrell; Vikas Goyal; Anne B. Chang; Keith Grimwood; Michael Cheng; Stephanie T. Yerkovich; Katherine J. Baines (Journal of Molecular Medicine, 2026)
Acute respiratory exacerbations in bronchiectasis are important as they impair quality of life and are associated with accelerated lung function decline. Yet, no validated methods exist to identify children at increased risk of exacerbations. We therefore determined if peripheral blood gene expression (GE) signatures can identify those at risk of an impending exacerbation. Thirty-one children with bronchiectasis had RNA extracted from peripheral blood collected whilst they were clinically stable, with 22 having an exacerbation during the next 3 months. Microarray assays using the HumanHT-12 v4.0 Expression BeadChip identified differentially expressed genes ( p value ≤ 0.05, fold change > 1.5). The top targets were verified using real-time quantitative polymerase chain reaction (rt-qPCR) assays, and receiver operating characteristics and area under the curve (AUC) were assessed. Functional analysis of these genes was performed using Ingenuity Pathway Analysis. Overall, 647 entities were significantly dysregulated ( p < 0.05) in the exacerbation group ( n = 22), and pathway analysis identified neutrophil degranulation as the dominant affected pathway, which was also significantly inhibited ( p < 0.001). Forty entities (32 genes) were associated with a future exacerbation ( p ≤ 0.05, fold change ≥ 1.5) and six genes ( ANXA3 , ALAS2 , DEFA1 , ALPL , SNCA , PROK2 ) were verified using RT-qPCR (all p < 0.04) as the most discriminatory. DEFA1 and ANXA3 had the highest AUC (0.92, 95% confidence interval [CI] 0.82–1.00, and 0.87, 95% CI 0.73–1.00, respectively). We identified neutrophil-associated genes from peripheral blood that could be potential biomarkers for children with bronchiectasis at increased risk of exacerbations during the next 3 months. These GE signatures warrant further investigation and validation in larger, independent cohorts. Key messages Exacerbations in paediatric bronchiectasis are important. Peripheral blood gene expression may help identify children at risk of exacerbations. Six neutrophil-associated genes were associated with a future exacerbation. Identifying predictive gene expression signatures warrants further investigation.

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Hydrodynamic and sedimentary processes in sedimentation fields: the requirement for continued maintenance to preserve restored intertidal habitat - Jonathan Dale; Cai J.T. Ladd; Michelle Farrell; Michael P. Kennedy; Gabriela Ciappara; Chloe James; Iain Fairley (Journal of Environmental Management, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The CALHM1 blocker CGP37157 increases seizure severity during status epilepticus in adult mice - Meghma Mitra; Amaya Sanz Rodriguez; Norman Delanty; Alan Beausang; Francesca M. Brett; Michael A. Farrell; Jane Cryan; Donncha F. O’Brien; David Henshall; Maria F. Cano-Abad; Tobias Engel (Purinergic Signalling, 2025)
Epilepsy is one of the most common chronic brain diseases affecting up to 70 million people worldwide. Major challenges of epilepsy treatment include the high pharmacoresistance in patients and the lack of disease-modification. Extracellular adenosine 3’triphosphate (ATP), a key neurotransmitter in the activation of the purinergic signalling system, is increasingly recognized to contribute to pathological brain hyperexcitability in epilepsy. Consequently, targeting ATP-release mechanisms may constitute a new therapeutic strategy for seizure control and epilepsy. The calcium channel, Calcium Homeostasis Modulator 1 (CALHM1), a voltage-gated, non-selective ion channel that permits the passage of various cations and small molecules, is expressed in neurons and plays an essential role during neuronal excitability and neurotransmission. In addition to ions, CALHM1 also allows the passage of ATP into the extracellular space, activating thereby purinergic receptors. Here, we tested if the pharmacological blocking of CALHM1 via CGP37157 (7-chloro-5-(2-chlorophenyl)-3,5-dihydro-4,1-benzothiazepin-2-(1H)-one) alters the severity of intra-amygdala kainic acid-induced status epilepticus. Our results show that CGP37157 increased the severity of seizures during status epilepticus. In addition, CALHM1 protein levels are down-regulated in the hippocampus in epileptic mice and Temporal Lobe Epilepsy (TLE) patients. In summary, our results identify CALHM1 as a new contributor to seizures and suggest targeting of CALHM1 as new treatment strategy for epilepsy.

Microbial community response to spent mushroom substrate composting methods by phospholipid fatty acid analysis - Siobhan N. Jordan; Michael P. Farrell; Caroline T. Gilleran Stephens (Biocatalysis and Agricultural Biotechnology, 2025)

Abundance Trends of Pacific Salmon During a Quarter Century of ESA Protection - Michael J. Ford; Steven T. Lindley; Katie A. Barnas; Andrew O. Shelton; Brian C. Spence; Laurie A. Weitkamp; Damon M. Holzer; David A. Boughton; Elizabeth E. Holmes; James M. Myers; Chris E. Jordan; Heidi Fish; et al. (Fish and Fisheries, 2025)
Between 1989 and 2007, 28 Distinct Population Segments (DPS) of Pacific salmon ( Oncorhynchus spp.) spawning in rivers in California and the Pacific Northwest (Oregon, Washington, Idaho) were listed (protected) under the US Endangered Species Act (ESA). In the roughly 25 years since then, considerable efforts have been made to recover these populations, but no DPS has increased sufficiently to be delisted. We evaluated abundance trends of ESA‐listed Pacific salmon DPS, along with DPS that were not ESA‐listed. Our goal was to evaluate whether protected DPS increased in abundance during the period of protection (nominally 1995–2020 in our study), either in absolute terms or relative to the unprotected DPS. A majority of the protected DPS had increasing abundance trends over this time period, and protected populations had higher median trends than non‐protected populations of the same species. Geographically, populations in the Pacific Northwest had higher median trends than those in California. Among species of protected populations, Chinook salmon ( O. tshawytscha ), chum salmon ( O. keta ) and sockeye salmon ( O. nerka ) had higher median trends than coho salmon ( O. kisutch ) and steelhead (anadromous O. mykiss ). For most DPS (listed and unlisted), trends in harvest rates and hatchery releases were relatively stable during the same time period, whereas trends in indicators related to freshwater and marine climate were generally negative for salmon. Our results suggest that salmon recovery actions may have helped to stabilise and increase protected DPS, but most remain far below their recovery goals.

Factors affecting short-term post-release survival probability of Lake Trout implanted with acoustic telemetry transmitters - Alexander J. Gatch; Dimitry Gorsky; Kyle T. Morton; R. Josephine Johnson; Collin J. Farrell; Timothy B. Johnson; Emma J. Bloomfield; Brent Metcalfe; Jessica Goretzke; Michael Connerton; Sarah M. Larocque; Jonathan D. Midwood; et al. (Fisheries Research, 2025)

Resprout survival and vigour in urban woody plantings are related to water availability, climate of origin, and root morphology - Alexandra Babington; Michael Hughes; Claire Farrell; Jane Chambers; Rachel J. Standish (Urban Forestry & Urban Greening, 2025)

Determinants of antimicrobial resistance in biosolids: A systematic review, database, and meta-analysis - Joanna Ciol Harrison; Grace V. Morgan; Aditya Kuppravalli; Nicole Novak; Michael Farrell; Sienna Bircher; Emily Garner; Nicholas J. Ashbolt; Amy Pruden; Rebecca L. Muenich; Treavor H. Boyer; Clinton Williams; et al. (Science of The Total Environment, 2024)

Biotransformation of 6:2/4:2 fluorotelomer alcohols by Dietzia aurantiaca J3: Enzymes and proteomics - Shefali Bhardwaj; Matthew Lee; Denis O'Carroll; James McDonald; Keith Osborne; Stuart Khan; Russell Pickford; Nicholas Coleman; Casey O’Farrell; Sarah Richards; Michael J. Manefield (Journal of Hazardous Materials, 2024)

Variability in surface CO2 flux: Implication for monitoring surface emission from geothermal fields - Tsung-Han Jimmy Yang; Isabelle Chambefort; Michael Rowe; Agnes Mazot; Anya Seward; Cynthia Werner; Tobias Fischer; Jun Seastres; Farrell Siega; Nick Macdonald; Thomas Brakenrig; Lauren Coup; et al. (Geothermics, 2024)

Flow induced attrition of cellulose nanocrystals - Bradley P. Sutliff; Connor Farrell; Stephen M. Martin; Michael J. Bortner (Carbohydrate Polymers, 2023)

Preference for multi-layered, flowering, woody streetscape plantings in a mediterranean-type climate - Alexandra Babington; Michael Hughes; Claire Farrell; Jane Chambers; Rachel J. Standish (Urban Forestry & Urban Greening, 2023)

Gill net catchability of walleye (Sander vitreus): Are provincial standards suitable for estimating adult density outside the region? - Adam G. Hansen; Michael W. Miller; Erik T. Cristan; Collin J. Farrell; Paul Winkle; Mandi M. Brandt; Kyle D. Battige; Jesse M. Lepak (Fisheries Research, 2023)

Assessing Antigen-Adjuvant Complex Stability Against Physical Stresses By wNMR - Marc B. Taraban; Katharine T. Briggs; Yihua Bruce Yu; Michael T. Jones; Lindsey Rosner; Akhilesh Bhambhani; Donna M. Williams; Christopher Farrell; Mikhail Reibarkh; Yongchao Su (Pharmaceutical Research, 2023)

A pilot study investigating feasibility of mainstreaming germline BRCA1 and BRCA2 testing in high-risk patients with breast and/or ovarian cancer in three tertiary Cancer Centres in Ireland - Terri Patricia McVeigh; Karl J. Sweeney; Donal J. Brennan; Una M. McVeigh; Simon Ward; Ann Strydom; Sheila Seal; Katherine Astbury; Paul Donnellan; Joanne Higgins; Maccon Keane; Michael J. Kerin; et al. (Familial Cancer, 2023)

From COVID-19 to Green Recovery with natural capital accounting - Michael Vardon; Paul Lucas; Steve Bass; Matthew Agarwala; Andrea M. Bassi; Diane Coyle; Anthony Dvarskas; Catherine A. Farrell; Oliver Greenfield; Steven King; Martin Lok; Carl Obst; et al. (Ambio, 2023)
The COVID-19 pandemic and related social and economic emergencies induced massive public spending and increased global debt. Economic recovery is now an opportunity to rebuild natural capital alongside financial, physical, social and human capital, for long-term societal benefit. Yet, current decision-making is dominated by economic imperatives and information systems that do not consider society’s dependence on natural capital and the ecosystem services it provides. New international standards for natural capital accounting (NCA) are now available to integrate environmental information into government decision-making. By revealing the effects of policies that influence natural capital, NCA supports identification, implementation and monitoring of Green Recovery pathways, including where environment and economy are most positively interlinked.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Practising everyday climate cultures: understanding the cultural politics of climate change - Michael K. Goodman; Julie Doyle; Nathan Farrell (Climatic Change, 2020)

The cultural politics of climate branding: Project Sunlight, the biopolitics of climate care and the socialisation of the everyday sustainable consumption practices of citizens-consumers - Julie Doyle; Nathan Farrell; Michael K. Goodman (Climatic Change, 2020)

COVID-19 and Pacific food system resilience: opportunities to build a robust response - Penny Farrell; Anne Marie Thow; Jillian Tutuo Wate; Nichol Nonga; Penina Vatucawaqa; Tom Brewer; Michael K. Sharp; Anna Farmery; Helen Trevena; Erica Reeve; Hampus Eriksson; Itziar Gonzalez; et al. (Food Security, 2020)

Effects of plant functional group removal on structure and function of soil communities across contrasting ecosystems - Nicolas Fanin; Paul Kardol; Mark Farrell; Anne Kempel; Marcel Ciobanu; Marie‐Charlotte Nilsson; Michael J. Gundale; David A. Wardle (Ecology Letters, 2019)
Loss of plant diversity has an impact on ecosystems worldwide, but we lack a mechanistic understanding of how this loss may influence below‐ground biota and ecosystem functions across contrasting ecosystems in the long term. We used the longest running biodiversity manipulation experiment across contrasting ecosystems in existence to explore the below‐ground consequences of 19 years of plant functional group removals for each of 30 contrasting forested lake islands in northern Sweden. We found that, against expectations, the effects of plant removals on the communities of key groups of soil organisms (bacteria, fungi and nematodes), and organic matter quality and soil ecosystem functioning (decomposition and microbial activity) were relatively similar among islands that varied greatly in productivity and soil fertility. This highlights that, in contrast to what has been shown for plant productivity, plant biodiversity loss effects on below‐ground functions can be relatively insensitive to environmental context or variation among widely contrasting ecosystems.

Reflex regulation of breathing by the paratrigeminal nucleus via multiple bulbar circuits - Alexandria K. Driessen; Michael J. Farrell; Mathias Dutschmann; Davor Stanic; Alice E. McGovern; Stuart B. Mazzone (Brain Structure and Function, 2018)

Applying species distribution modelling to improving conservation based decisions: a gap analysis of Trinidad and Tobago’s endemic vascular plants - Joshua A. Spiers; Michael P. Oatham; Luke V. Rostant; Aidan D. Farrell (Biodiversity and Conservation, 2018)

Responses of a Federally Endangered Songbird to Understory Thinning in Oak-Juniper Woodlands - Ashley M. Long; Mike E. Marshall; Michael L. Morrison; K. Brian Hays; Shannon L. Farrell (Environmental Management, 2017)

Evidence for multiple sensory circuits in the brain arising from the respiratory system: an anterograde viral tract tracing study in rodents - Alice E. McGovern; Nicholas Davis-Poynter; Seung-Kwon Yang; David G. Simmons; Michael J. Farrell; Stuart B. Mazzone (Brain Structure and Function, 2015)

Mouse genome annotation by the RefSeq project - Kelly M. McGarvey; Tamara Goldfarb; Eric Cox; Catherine M. Farrell; Tripti Gupta; Vinita S. Joardar; Vamsi K. Kodali; Michael R. Murphy; Nuala A. O’Leary; Shashikant Pujar; Bhanu Rajput; Sanjida H. Rangwala; et al. (Mammalian Genome, 2015)
Complete and accurate annotation of the mouse genome is critical to the advancement of research conducted on this important model organism. The National Center for Biotechnology Information (NCBI) develops and maintains many useful resources to assist the mouse research community. In particular, the reference sequence (RefSeq) database provides high-quality annotation of multiple mouse genome assemblies using a combinatorial approach that leverages computation, manual curation, and collaboration. Implementation of this conservative and rigorous approach, which focuses on representation of only full-length and non-redundant data, produces high-quality annotation products. RefSeq records explicitly link sequences to current knowledge in a timely manner, updating public records regularly and rapidly in response to nomenclature updates, addition of new relevant publications, collaborator discussion, and user feedback. Whole genome re-annotation is also conducted at least every 12–18 months, and often more frequently in response to assembly updates or availability of informative data. This article highlights key features and advantages of RefSeq genome annotation products and presents an overview of NCBI processes to generate these data. Further discussion of NCBI’s resources highlights useful features and the best methods for accessing our data.

Low Concentrations of Contaminants in an Invasive Cyprinid, the Rudd, in a Great Lakes Area of Concern - Kevin L. Kapuscinski; John M. Farrell; Gordon Paterson; Michael A. Wilkinson; Lawrence C. Skinner; Wayne Richter; Anthony J. Gudlewski (Bulletin of Environmental Contamination and Toxicology, 2014)

Estimating the maple syrup production potential of American forests: an enhanced estimate that accounts for density and accessibility of tappable maple trees - Michael Farrell (Agroforestry Systems, 2013)

Feeding patterns and population structure of an invasive cyprinid, the rudd Scardinius erythrophthalmus (Cypriniformes, Cyprinidae), in Buffalo Harbor (Lake Erie) and the upper Niagara River - Kevin L. Kapuscinski; John M. Farrell; Michael A. Wilkinson (Hydrobiologia, 2012)

Clinical correlation and molecular evaluation confirm that the MLH1 p.Arg182Gly (c.544A>G) mutation is pathogenic and causes Lynch syndrome - Michael P. Farrell; David J. Hughes; Ian R. Berry; David J. Gallagher; Emily A. Glogowski; Stewart J. Payne; Michael J. Kennedy; Róisín M. Clarke; Susan A. White; Cian B. Muldoon; Fiona Macdonald; Pauline Rehal; et al. (Familial Cancer, 2012)

High-resolution array CGH defines critical regions and candidate genes for microcephaly, abnormalities of the corpus callosum, and seizure phenotypes in patients with microdeletions of 1q43q44 - Blake C. Ballif; Jill A. Rosenfeld; Ryan Traylor; Aaron Theisen; Patricia I. Bader; Roger L. Ladda; Susan L. Sell; Michelle Steinraths; Urvashi Surti; Marianne McGuire; Shelley Williams; Sandra A. Farrell; et al. (Human Genetics, 2012)

Silviculture and Forest Ecology - David Mercker; Ryan Blair; Don Tyler; Theresa Jain; Russell Graham; Donald Rockwood; Nicholas Koch; Jeremy Brawner; Omar Carrero; Kristofer Covey; Alex Barrett; Mark Ashton; et al. (Journal of Forestry, 2011)
2Over the past several decades, federal incentive programs have encouraged the restoration of bottomland forests throughout the West Gulf Coastal Plain (WGCP) and the Lower Mississippi Alluvial Valley (LMAV). Programs such as the Conservation Reserve (CRP) and Wetlands Reserve (WRP) Programs have been marginally successful (Stanturf et al. 2001). Foresters and contractors often follow conventional tree planting procedures that are well established for upland sites, but prove problematic in bottomlands. High water tables, soil drainage and compaction, overland flooding and diverse soil properties make species selection difficult. Slight changes in topography and soil structure often have a dramatic effect on survival and growth of planted oak seedlings (Hodges and Schweitzer 1979). This project documented the survival and growth of six-year old seedlings that were established on a bottomland site in 2004, located at the West Tennessee Research and Education Center, Jackson, Tennessee. The purpose was to determine how soil drainage as indicated by mottling (specifically, the point of 50 percent gray color throughout the soil profile) affects the survival and growth of bottomland oak species. The findings suggest that practitioners plant Nuttall, pin and overcup oaks in poorly drained soils. As the drainage improves, begin mixing in willow oak. In the best drained soils (if they exist), finish by including water, swamp chestnut, swamp white, Shumard, cherrybark and bur oaks. Potential species diversity should expand as the soil drainage improves.

Safeguarding Biodiversity and Ecosystem Services in the Little Karoo, South Africa - BENIS N. EGOH; BELINDA REYERS; JOSIE CARWARDINE; MICHAEL BODE; PATRICK J. O'FARRELL; KERRIE A. WILSON; HUGH P. POSSINGHAM; MATHIEU ROUGET; WILLEM De LANGE; DAVID M. RICHARDSON; RICHARD M. COWLING (Conservation Biology, 2010)
Global declines in biodiversity and the widespread degradation of ecosystem services have led to urgent calls to safeguard both. Responses to this urgency include calls to integrate the needs of ecosystem services and biodiversity into the design of conservation interventions. The benefits of such integration are purported to include improvements in the justification and resources available for these interventions. Nevertheless, additional costs and potential trade‐offs remain poorly understood in the design of interventions that seek to conserve biodiversity and ecosystem services. We sought to investigate the synergies and trade‐offs in safeguarding ecosystem services and biodiversity in South Africa's Little Karoo. We used data on three ecosystem services—carbon storage, water recharge, and fodder provision—and data on biodiversity to examine several conservation planning scenarios. First, we investigated the amount of each ecosystem service captured incidentally by a conservation plan to meet targets for biodiversity only while minimizing opportunity costs. We then examined the costs of adding targets for ecosystem services into this conservation plan. Finally, we explored trade‐offs between biodiversity and ecosystem service targets at a fixed cost. At least 30% of each ecosystem service was captured incidentally when all of biodiversity targets were met. By including data on ecosystem services, we increased the amount of services captured by at least 20% for all three services without additional costs. When biodiversity targets were reduced by 8%, an extra 40% of fodder provision and water recharge were obtained and 58% of carbon could be captured for the same cost. The opportunity cost (in terms of forgone production) of safeguarding 100% of the biodiversity targets was about US$500 million. Our results showed that with a small decrease in biodiversity target achievement, substantial gains for the conservation of ecosystem services can be achieved within our biodiversity priority areas for no extra cost.

From the Great Lakes flows a Great River: overview of the St. Lawrence River ecology supplement - Jérôme Marty; Michael R. Twiss; Jeffrey J. Ridal; Yves de Lafontaine; John M. Farrell (Hydrobiologia, 2010)

Assessment of habitat and predator effects on dwarf rockfishes (Sebastes spp.) using multi model inference - Michael R. O’Farrell; Mary M. Yoklavich; Milton S. Love (Environmental Biology of Fishes, 2009)

Comparative expression and transcript initiation of three peach dehydrin genes - Carole Leavel Bassett; Michael E. Wisniewski; Timothy S. Artlip; Greg Richart; John L. Norelli; Robert E. Farrell (Planta, 2009)

Connectivity, sustainability, and yield: bridging the gap between conventional fisheries management and marine protected areas - Louis W. Botsford; Daniel R. Brumbaugh; Churchill Grimes; Julie B. Kellner; John Largier; Michael R. O’Farrell; Stephen Ralston; Elaine Soulanille; Vidar Wespestad (Reviews in Fish Biology and Fisheries, 2009)

Rapid transcriptional response of apple to fire blight disease revealed by cDNA suppression subtractive hybridization analysis - John L. Norelli; Robert E. Farrell; Carole L. Bassett; Angela M. Baldo; Donna A. Lalli; Herb S. Aldwinckle; Michael E. Wisniewski (Tree Genetics & Genomes, 2009)

Effect of planting stocktype and cultivation treatment on the establishment of Norway spruce on cutaway peatlands - Florence Renou-Wilson; Michael Keane; E. P. Farrell (New Forests, 2008)

Early performance of native birch (Betula spp.) planted on cutaway peatlands: influence of species, stock types and seedlings size - Florence Renou; Úna Scallan; Michael Keane; E. P. Farrell (European Journal of Forest Research, 2007)

Continuous measurement of oxygen tensions in the air-breathing organ of Pacific tarpon (Megalops cyprinoides) in relation to aquatic hypoxia and exercise - Roger S. Seymour; Anthony P. Farrell; Keith Christian; Timothy D. Clark; Michael B. Bennett; Rufus M. G. Wells; John Baldwin (Journal of Comparative Physiology B, 2007)

Above- and belowground biomass measurements in an unthinned stand of Sitka spruce (Picea sitchensis (Bong) Carr.) - Carly Green; Brian Tobin; Michael O’Shea; Edward P. Farrell; Kenneth A. Byrne (European Journal of Forest Research, 2007)

Effects of geometric isomerism in dinuclear antitumor platinum complexes on their interactions with N-acetyl-L-methionine - Michael E. Oehlsen; Alexander Hegmans; Yun Qu; Nicholas Farrell (JBIC Journal of Biological Inorganic Chemistry, 2005)

Effects of geometric isomerism in dinuclear antitumor platinum complexes on their interactions with N-acetyl-L-methionine - Michael E. Oehlsen; Alexander Hegmans; Yun Qu; Nicholas Farrell (JBIC Journal of Biological Inorganic Chemistry, 2005)

The pharmacokinetics of erythropoietin in the cerebrospinal fluid after intravenous administration of recombinant human erythropoietin - Anargyros Xenocostas; Wing K. Cheung; Francis Farrell; Cindy Zakszewski; Marian Kelley; Andrzej Lutynski; Michael Crump; Jeffrey H. Lipton; Thomas L. Kiss; Catherine Y. Lau; Hans A. Messner (European Journal of Clinical Pharmacology, 2005)

Exposure to solar radiation increases damage to both host tissues and algal symbionts of corals during thermal stress - Michael P. Lesser; Julianne H. Farrell (Coral Reefs, 2004)

Somatic energy of sockeye salmon Oncorhynchus nerka at the onset of upriver migration: a comparison among ocean climate regimes - Glenn T. Crossin; Scott G. Hinch; Anthony P. Farrell; David A. Higgs; Michael C. Healey (Fisheries Oceanography, 2004)
We examined somatic energy patterns in two stocks (Chilko and Early Stuart) of adult Fraser River (British Columbia, Canada) sockeye salmon ( Oncorhynchus nerka ), collected at the end of their ocean residency, spanning years across different climate regimes. Both stocks had high levels of somatic energy in years with high open ocean productivity (1956, 1957, 2001 and 2002), and relatively low levels in years with poor open ocean productivity (1999 and 2000). For Early Stuart sockeye, energy levels in 1999 and 2000 were approximately 15% lower (∼1.5 MJ kg −1 ) than that in the 1950s, an amount of energy equivalent to that necessary for migrating 600 km upriver. In recent years (2001 and 2002), energy levels have increased by about 9% for both stocks. Low energy levels at the onset of upriver migration, particularly in years of energetically demanding in‐river conditions, such as high flows or temperatures, are likely to contribute to prespawning and en route mortality in Fraser sockeye.

Green‐fluorescent proteins in Caribbean corals - Charles H. Mazel; Michael P. Lesser; Maxim Y. Gorbunov; Thomas M. Barry; Julianne H. Farrell; Kevin D. Wyman; Paul G. Falkowski (Limnology and Oceanography, 2003)
Fluorescent pigments in several Indo‐Pacific and Caribbean anthozoans have recently been identified as proteins related to the Green‐fluorescent protein (GFP) of the hydromedusa Aequorea victoria . Here we show that GFP is widely distributed in many Caribbean species. The fluorescence excitation and emission spectra for the pigment are similar to those reported elsewhere for coral and noncoral GFP and the fluorescence quantum yield is estimated to be 35%. Spectral and molecular characterization of the isolated protein clearly show it to be GFP, and laboratory and in situ fluorescence measurements and Western blot analysis show that it is widespread. Bathymetric studies of GFP content using Western blots for the ecologically important congeneric corals Montastraea faveolata and Montastraea cavernosa show that there is no significant correlation between depth and GFP concentration. Nucleotide sequence data of GFP from M. faveolata and M. cavernosa show 88.2% sequence homology with each other and 46.4% homology with A. victoria GFP, whereas the percent homology with A. victoria at the amino acid level was 31.1 and 28.4% for M. cavernosa and M. faveolata , respectively, and 82.7% with each other. Measurements of reflectance and of the excitation spectrum for chlorophyll fluorescence in GFP‐containing corals indicate that GFP absorption, emission, and reflection have negligible impact on the level of solar radiation reaching the zooxanthellae and therefore play no role in coral photosynthesis by either addition or removal of photons.

Swimming patterns and behaviour of upriver-migrating adult pink (Oncorhynchus gorbuscha) and sockeye (O. nerka) salmon as assessed by EMG telemetry in the Fraser River, British Columbia, Canada - Scott G. Hinch; Emily M. Standen; Michael C. Healey; Anthony P. Farrell (Hydrobiologia, 2002)